Critical Reflexivity in Political Ecology Research: How can the Covid-19 Pandemic Transform us Into Better Researchers? - Gonda, Noémi; Leder, Stephanie; González-Hidalgo, Marien; Chiwona-Karltun, Linley; Stiernström, Arvid; Hajdu, Flora; Fischer, Klara; Asztalos Morell, Ildikó; Kadfak, Alin; Arvidsson, Anna (Frontiers in Human Dynamics, 2021)
It is not just the world but our ways of producing knowledge that are in crisis. The Covid-19 pandemic has exposed our interconnected vulnerabilities in ways never seen before while underscoring the need for emancipation in particular from the hegemonic knowledge politics that underpin “business-as-usual” academic research that have both contributed to and failed to address the systemic challenges laid bare by the pandemic. Political ecologists tasked with knowledge generation on vulnerabilities and their underlying power processes are particularly well placed to envision such emancipatory processes. While pausing physically due to travel restrictions, as researchers in political ecology and rural development at the same university department, we want to make a stop to radically rethink our intellectual engagements. In this article, we aim to uncover “sanitized” aspects of research encounters, and theorize on the basis of anecdotes, feelings and informal discussions—“data” that is often left behind in fieldwork notes and personal diaries of researchers—, the ways in which our own research practices hamper or can be conducive to emancipation in times of multiple interconnected health, political, social, and environmental crises. We do so through affective autoethnography and resonances on our research encounters during the pandemic: with people living in Swedish Sapmi, with African students in our own “Global North” university department and with research partners in Nepal. We use a threefold focus on interconnectedness, uncertainty and challenging hegemonic knowledge politics as our analytical framework. We argue that acknowledging the roles of emotions and affect can 1) help embrace interconnectedness in research encounters; 2) enable us to work with uncertainty rather than “hard facts” in knowledge production processes; and 3) contribute to challenging hegemonic knowledge production. Opening up for emotions in research helps us to embrace the relational character of vulnerability as a pathway to democratizing power relations and to move away from its oppressive and colonial modes still present in universities and research centers. Our aim is to contribute to envisioning post-Covid-19 political ecology and rural development research that is critically reflexive and that contributes to the emergence of a new ethics of producing knowledge.